Clonal composition and persistence of antigen‐specific circulating T follicular helper cells. Issue 2 (25th December 2022) - Hu, Mengyun; Notarbartolo, Samuele; Foglierini, Mathilde; Jovic, Sandra; Mele, Federico; Jarrossay, David; Lanzavecchia, Antonio; Cassotta, Antonino; Sallusto, Federica
Abstract: T follicular helper (TFH ) cells play an essential role in promoting B cell responses and antibody affinity maturation in germinal centers (GC). A subset of memory CD4 + T cells expressing the chemokine receptor CXCR5 has been described in human blood as phenotypically and clonally related to GC TFH cells. However, the antigen specificity and relationship of these circulating TFH (cTFH ) cells with other memory CD4 + T cells remain poorly defined. Combining antigenic stimulation and T cell receptor (TCR) Vβ sequencing, we found T cells specific to tetanus toxoid (TT), influenza vaccine (Flu), or Candida albicans ( C.alb ) in both cTFH and non‐cTFH subsets, although with different frequencies and effector functions. Interestingly, cTFH and non‐cTFH cells specific for C.alb or TT had a largely overlapping TCR Vβ repertoire while the repertoire of Flu‐specific cTFH and non‐cTFH cells was distinct. Furthermore, Flu‐specific but not C.alb ‐specific PD‐1 + cTFH cells had a "GC TFH ‐like" phenotype, with overexpression of IL21, CXCL13, and BCL6 . Longitudinal analysis of serial blood donations showed that Flu‐specific cTFH and non‐cTFH cells persisted as stable repertoires for years. Collectively, our study provides insights on the relationship of cTFH with non‐cTFH cells and on the heterogeneity and persistence of antigen‐specific human cTFH cells. Abstract : An in‐depth T cell receptor Vβ repertoire analysis of human blood CD4 + T helper cells specific for different microbial antigens (i.e. influenza vaccine, tetanus toxoid, and Candida albicans ) revealed that circulating T follicular helper cells are heterogeneous in phenotype and persistence.